The The Efforts of the Samapta Unit Through the Blue Light PatroL in Realizing Safe and Conducive Harkamtibmas in the Legal Area of the Kudus Police - Revaldo Cahyo Prakoso (Tanggon Kosala, 2023)
The writing of this final assignment is motivated by the number of crimes that have increased over the past few years, especially theft crimes and crimes against children. This crime often occurs because of the perpetrator's poor financial condition, bad environment and association. Criminals carry out their actions at night or in quiet places away from crowds. The purpose of writing this final project is : To describe the mechanism for implementing Blue Light Patrol Samapta Unit which is carried out in the Kudus Police jurisdiction To analyze the efforts of Blue Light Patrol Samapta Unit in realizing security and order maintenance To describe the influence of Blue Light Patrol Samapta Unit in creating security and order maintenance which safe and conducive The theory used in writing this thesis is the Management Theory of P.O.A.C. by George R. Terry and 5M Theory of Management by Harrington Emerson. While the concepts used are the Samapta Unit Concept, the Patrolling Concept, the security and order Concept, the Safe and Conducive Concept. The method of writing this final assignment is descriptive qualitative with data sources of interviews, observation and document studies. The results of this final project explain : The implementation of the Blue Light Patrol was not in accordance with the procedure Human resources less than standard None of the officers have received Education and Development The fuel budget is not transparent Lack of supervision for members Lack of seriousness and professionalism of members The Samapta Unit efforts of the Kudus Police are considered to be still not optimal, so it is recommended to make a map of regional vulnerability characteristics, regulate zone patrol activities, apply Whatsapp Share Locations, Timestamp Cameras and install Dash Cameras on patrol vehicles and make technical instructions for implementing Blue Light Patrol.